Arrested Puberty in a Young Adult With a Macroprolactinoma: Case Report and Literature Review - Sánchez M.; Otazú M.; Furtenbach P.; Piñeyro M. (Case Reports in Endocrinology)
Prolactinoma is the most common pituitary tumor, with clinical presentations varying according to sex, age of onset, tumor size, and prolactin (PRL) levels. These tumors are rare in the pediatric and adolescent populations. Hyperprolactinemia leads to hypogonadotropic hypogonadism, resulting in reproductive, metabolic, sexual, and skeletal consequences that can affect puberty development. Here, we present the case of a 23-year-old male patient diagnosed with arrested puberty secondary to a macroprolactinoma. The clinical presentation, diagnostic approach, therapeutic management, and a literature review are discussed.